Efficacy of Coronary Computed Tomography Angiography for the De Novo Detection of Chronic Total Occlusion Prior to Coronary Angiography: A Preliminary and Retrospective Study - Lee, Dae Hyun; Thiruvengadam, Swetha Kambhampati; Mohammed, Mahad; Goli, Rakesh; Thiemann, David; Lawson, Barbara D.; Resar, Jon R.; Mohanty, Bibhu D. (International Journal of Angiology, 2020)
Coronary computed tomography angiography (CCTA) offers high-resolution anatomic characterization of the coronary vasculature but may be suboptimal for lesions dependent on real-time visualization of flow including chronic total occlusion (CTO). In CTOs, heavy calcification and distal vessel opacification from collateralization may confound luminal assessment. Several studies have examined the role of CCTA in characterizing known CTOs to guide percutaneous coronary intervention (PCI). However, the efficacy of CCTA in the de novo diagnosis of CTOs prior to coronary angiography (CAG) has not been demonstrated. A total of 233 consecutive patients who presented for CAG within a 3-month period of having CCTA were retrospectively reviewed. Those patients with prior diagnosis of CTO or prior bypass of the occluded vessels were excluded. Sensitivity and specificity analysis of CCTA in identifying CTOs using CAG as the gold standard was performed. The prevalence of CTO was 21.11% in the population that met criteria for analysis (n = 199). The sensitivity of CCTA in predicting CTO was 57.1%, while the specificity was 96.8%. The positive predictive value and negative predictive value of CCTA in detection of CTO were 82.8 and 89.4%, respectively. Our study shows that CCTA has excellent specificity but poor sensitivity in the detection of CTO thus limiting its clinical use in de novo diagnosis. Further studies to determine the effect of de novo CTO diagnosis on clinically important procedural factors, such as radiation exposure, contrast use, and need for repeat procedures, are warranted and may implicate a role for CCTA in this setting.
Keywords: coronary computed tomography angiography; chronic total occlusion; coronary intervention; coronary occlusion; coronary angiography